Genderlect Styles Pada Komunikasi Interpersonal Suami Istri Dalam Film (Analisis Naratif Kualitatif Pada Film â€œMilly & Mametâ€) - Alexandrea, Bella Christy; Idaman, Nur (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2023)
Film is an entertainment medium that is able to help convey messages to thepublic in the form of effective audio-visual. Films can also tell us something thathappened in real life or related to the social reality that exists in society. The film "Millyand Mamet" contains gender values that occur in husband and wife relationships as wellas interpersonal communication which contains a difference between male and femalelanguage styles which is interesting to study.The theory in this study uses the theory of mass media reality construction andsymbolic interaction theory. The method used in this study is Nick Lacey andGillespie's narrative analysis which has five divisions of narration to find out thestoryline of a film. The purpose of this research is to find out the truth about thedifferences in language style between men and women in a film which is analyzed usinga narrative analysis technique.The results of the research conducted, in each of the five sections of narrativeanalysis, there are points of genderlect styles found in every dialogue and symbolicinteraction that occurs in the film Milly and Mamet.